2019
DOI: 10.1177/0899764019868843
|View full text |Cite
|
Sign up to set email alerts
|

Do You Like What You See? How Nonprofit Campaigns With Output, Outcome, and Impact Effectiveness Indicators Influence Charitable Behavior

Abstract: This study contributes to recent discussions on voluntary disclosure as a signaling approach among nonprofit organizations and its effects on stakeholders’ decision-making. Focusing on nonprofit program effectiveness, we test how nonprofit campaigns providing information on three effectiveness indicators—outputs, outcomes, and impacts (as part of the logic framework)—influence donation and lending behavior. An online survey experiment ( N = 271) reveals that donors value outcome and impact indicators more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(104 reference statements)
0
13
0
2
Order By: Relevance
“…Perceptions of fundraising legitimacy can be promoted by the organization's effectiveness (impact on the cause; e.g., Bodem‐Schrotgens & Becker, 2020; Smith & McSweeney, 2007; Wiepking et al, 2012), efficiency (percentage of funds that go toward charitable projects compared to marketing and overheads; e.g., Gneezy et al, 2014; Tinkelman & Mankaney, 2007), alternative sources of funds (e.g., government grants; De Wit & Bekkers, 2017), and reputation based on factors like size, perceived quality, brand image, accreditation status, or trustworthiness (e.g., Bennett & Gabriel, 2000; Chapman, Hornsey & Mangan, Gillespie, et al, 2021; Hornsey et al, 2021; Sarstedt & Schloderer, 2010; Stebbins & Hartman, 2013).…”
Section: Charitable Triad Theory: Propositions and Evidencementioning
confidence: 99%
“…Perceptions of fundraising legitimacy can be promoted by the organization's effectiveness (impact on the cause; e.g., Bodem‐Schrotgens & Becker, 2020; Smith & McSweeney, 2007; Wiepking et al, 2012), efficiency (percentage of funds that go toward charitable projects compared to marketing and overheads; e.g., Gneezy et al, 2014; Tinkelman & Mankaney, 2007), alternative sources of funds (e.g., government grants; De Wit & Bekkers, 2017), and reputation based on factors like size, perceived quality, brand image, accreditation status, or trustworthiness (e.g., Bennett & Gabriel, 2000; Chapman, Hornsey & Mangan, Gillespie, et al, 2021; Hornsey et al, 2021; Sarstedt & Schloderer, 2010; Stebbins & Hartman, 2013).…”
Section: Charitable Triad Theory: Propositions and Evidencementioning
confidence: 99%
“…For an example of framing, Lewis and Small (2019) show that people donate less when the information provided is about the cost of units of output and the cost of a unit is cheaper (i.e., the cost of one mosquito net), but donate more when the information is expressed as cost-effectiveness, or units per dollar amounts (i.e., # nets provided per $). Effectiveness can also be framed by timing; when provided information about outputs (immediate effects), outcomes (medium-term effects) and impact (long-term effects) people prefer outcomes and impact information equally above output information (Bodem-Schrötgens & Becker, 2020). In another study, framing with a narrative that identified a victim raised larger donations than a gain-framed narrative or factual text in an online survey experiment on Amazon Mechanical Turk (Metzger & Günther, 2019) perhaps because of physiological responses to narratives within those solicitations (Barraza et al, 2015).…”
Section: Information About Effectivenessmentioning
confidence: 99%
“…People also donate more when receiving specific information about a charity's intervention, such as how donations will be used (Cryder et al, 2013). Moreover, donors respond positively to specific outcome and impact information (Karlan & Wood, 2017;Metzger & Günther, 2019;Levine Daniel & Eckerd, 2019;Bodem-Schrötgens & Becker, 2020).…”
Section: Literature and Hypothesesmentioning
confidence: 99%